Effects of different types of growth media on metabolite profiles (GCMS-based) of CHO-K1 cells expressing IGF-1 proteins - Mohamed Saberi, Salfarina Ezrina; Hashim, Yumi Zuhanis Has-Yun; Packeer Mohamed, Vasila; Amid, Azura; Ahmad Raus, Raha; Mel, Maizirwan; Gibney, Michael J.; Brennan, Lorraine; Al-Rubeai, Mohamed (2011)
The use of mammalian cell lines especially Chinese Hamster Ovary-K1 (CHO-K1) cells for expression of recombinant proteins with potential therapeutic use such as viral vaccines, monoclonal antibodies, recombinant glycoproteins and blood clotting factors has become increasingly prevalent. An efficient mammalian cell system for producing bioproducts should retain high cell viability and efficient use of energy sources as such the cell need to be supplied with sufficient and appropriate fuel so that energy is not limiting and metabolic load reduced. Optimizing productivity by CHO-K1 cells relies partly on understanding relationships between types of media used, culture growth behavior and productivity. CHO-KI cells producing insulin-like growth factor-I (IGF1) were obtained from ATCC. Cells were grown in T-flask and incubated at 37°C, 5% CO2 until 70-80% confluent in Ham’s F12 and RPMI 1640 respectively. Samples were taken at designated intervals for routine cell counting (Trypan Blue dye exclusion method), IGF-1 expression (ELISA kit R&D Sstems, Inc) and global metabolite analysis (Gas Chromatography Mass Spectrometry, GCMS). Conditioned media from each time point were spun down before subjecting to direct injection in GCMS. Deconvoluted data from GCMS was then transferred to SIMCA-P+12.0 for chemometric evaluation using Principal Component Analysis (PCA). Based on PCA of metabolites, different growth media have different effects on growth behavior even with the presence of different growth phases as cofounding factor. It is clearly seen that Ham’s F12 and RPMI 1640 were separated based on the metabolites. However, different types of media appeared not to affect IGF-1 production. In general, this offers insights of the interaction of culture environment, cell growth behavior and productivity leading to use of metabolomics approach for rationalizing and optimizing mammalian cell culture-based bioprocessing.